A Rare Evolution to Pneumopericardium in Patient with COVID-19 Pneumonia Treated with High Flow Nasal Cannula - Giorgio Emanuele Polistina; Maurizia Lanza; Camilla Di Somma; Anna Annunziata; Giuseppe Fiorentino (Medicina, 2021)
Infection with severe acute respiratory syndrome coronavirus 2 causes coronavirus disease 2019 (COVID-19) which was revealed an official pandemic by the World Health Organization on 11 March 2020. The current pandemic, the third of this decade, is the worst in terms of suffering and deaths related. COVID-19 represents an unprecedented challenge for medical communities and patients around the world. High-resolution computed tomography of the chest (HRCT) is a fundamental tool in both management and diagnosis of the disease. Imaging plays an essential role in the diagnosis of all the manifestations of the disease and its complications and the correct use and interpretation of imaging tests are essential. Pneumomediastinum has been reported rarely in COVID-19 patients. We were one of the first groups to share our experiences in uncommon parenchymal complications of COVID-19 with spontaneous pneumothorax and pneumomediastinum, but also with new-onset bronchiectasis and cysts. A finding of pneumopericardium is also unusual. We hereby report a rare case of spontaneous pneumopericardium in a patient with COVID-19 pneumonia treated only with a high-flow nasal cannula (HFNC).